Women's issues in Amy Tan's The Joy Luck Club - Wiener, Gary (Social issues in literature, 2008)
Presents essays that examine women's issues in "The Joy Luck Club," discussing such topics as gender and ethnic identity, female empowerment, cultural conflict, and stereotypes about immigrant women